Elementary Geometry for College Students (5th Edition)

Published by Brooks Cole
ISBN 10: 1439047901
ISBN 13: 978-1-43904-790-3

Appendix A - A.4 - Quadratic Equations - Exercises: 14

Answer

$x = \frac{3}{2}, -2$

Work Step by Step

$2x^{2} + x - 6= 0$ Find two numbers that multiply to $((-6) \times 2 = -12)$ and can be added together to get $1$. $= -3$ and $4$ $2x^{2} - 3x + 4x - 6= 0$ $x(2x - 3) + 2(2x - 3) = 0$ $(2x - 3)(x+2) = 0$ $x = \frac{3}{2}, -2$ $2x - 3 = 0$ $2x = 3$ $x = \frac{3}{2}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.